The Scenology of Landscape in The Quickening Maze by Adam Foulds (American & British Studies Annual, 2011)
This text presents various possibilities of looking at landscape from a literary perspective, allowing the possibilities of interpreting it as a literary text or a theatrical scene. Such theoretical claims are tested in the analysis of several characters from Adam Foulds’s novel The Quickening Maze.
Keywords: landscape as a cultural artefact; scenology of landscape; literary landscape; John Clare; Matthew Allen; Adam Foulds; The Quickening Maze